Criminal Hegemony in the Novel Lodan saka Segara Kidul by Kukuh S. Wibowo: Gramsci's Perspective - Wahyudi, Ahmad Rizky; Ahmadi, Anas (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
The connection between thuggery and power gives rise to a new face of politics laden with criminal hegemony. This concept is vividly depicted in the Javanese novel Lodan saka Segara Kidul (LSSK) by Kukuh S. Wibowo. Through a mystery-driven narrative, the novel exposes the transformation of Rahsana, a criminal gang leader, who changes his name to Hendarsa Prabancana and reinvents himself as a politician using slick yet effective hegemonic strategies. This research aims to reveal the representation of criminal hegemony in LSSK by Kukuh S. Wibowo through the lens of Gramsci’s theory, supported by other theories such as the normalization of crime, political oligarchy, self-image management, and more. The study employs a descriptive-qualitative method, emphasizing content analysis and literature review to examine novel narratives. This approach aims to identify forms of criminal hegemony, strategies for transitioning from crime to politics, and their societal impact. The findings demonstrate that Rahsana/Hendarsa utilizes wealth acquired through crime, money politics, and public image-building to gain legitimacy and maintain power. Hegemony does not manifest solely through physical domination but also through ideology that infiltrates social structures. These findings reflect how criminal practices can adapt within democratic systems and become part of legitimate political frameworks. This research contributes to enriching the study of Indonesian crime fiction while opening a critical discourse on the relationship between crime, politics, and the legitimization of power.